The knowledge of Polish primary care physicians about bariatric surgery - Piotr Major; Tomasz Stefura; Monika Jezierska-Kazberuk; Michał Wysocki; Michał Pędziwiatr; Magdalena Pisarska; Piotr Małczak; Artur Kacprzyk; Andrzej Budzyński (Videosurgery and Other Miniinvasive Techniques)
Introduction: The general practitioner (GP) can play a key role in this multi-disciplinary team, coordinating care provided by dietitians and surgeons, maximizing the potential benefits of surgery. Therefore, it seems important to verify changes in GPs’ knowledge about surgical treatment of obesity. Aim : To reassess knowledge of obesity surgical treatment among Polish primary care physicians and their willingness to improve it in the future. Material and methods: To assess the knowledge of Polish primary care physicians about surgical treatment of obesity, a prospective study, which included an anonymous online questionnaire, was conducted in the years 2015–2016. Results : Two hundred and six physicians answered the invitation. One hundred and sixty-six (81.8%) respondents were familiar with the indications for bariatric operation. The great majority of respondents, 198 (96.6%), were aware that bariatric surgery is efficient in the treatment of the metabolic syndrome. The study revealed a disproportion between the number of patients who would be potential candidates for bariatric treatment, who are currently under care of participating physicians, and the number of patients who are referred to a bariatric surgeon. Conclusions : Our study demonstrates that nowadays bariatric surgery is a recognized method of treatment, but physicians remain reluctant to refer their patients for surgical treatment of obesity. It was found that there is a large disproportion between the number of patients who are referred to a bariatric surgeon and the number of patients who require this treatment. It may be a result of lack of knowledge in the field of bariatric surgery.